2022
DOI: 10.1111/cge.14132
|View full text |Cite
|
Sign up to set email alerts
|

El‐Hattab‐Alkuraya syndrome caused by biallelic WDR45B pathogenic variants: Further delineation of the phenotype and genotype

Abstract: Homozygous pathogenic variants in WDR45B were first identified in six subjects from three unrelated families with global development delay, refractory seizures, spastic quadriplegia, and brain malformations. Since the initial report in 2018, no further cases have been described. In this report, we present 12 additional individuals from seven unrelated families and their clinical, radiological, and molecular findings. Six different variants in WDR45B were identified, five of which are novel. Microcephaly and gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 34 publications
(78 reference statements)
1
8
0
Order By: Relevance
“…Recently, our group published detailed clinical, molecular, and radiological features of 12 new subjects with El-Hattab-Alkuraya syndrome (Almannai et al, 2022). Similar to what was observed in the initial report, the main features of this syndrome in this cohort are GDD, spastic quadriplegia, microcephaly, and early onset and refractory epilepsy (Almannai et al, 2022).…”
Section: Wipi (Wdr B)supporting
confidence: 71%
See 2 more Smart Citations
“…Recently, our group published detailed clinical, molecular, and radiological features of 12 new subjects with El-Hattab-Alkuraya syndrome (Almannai et al, 2022). Similar to what was observed in the initial report, the main features of this syndrome in this cohort are GDD, spastic quadriplegia, microcephaly, and early onset and refractory epilepsy (Almannai et al, 2022).…”
Section: Wipi (Wdr B)supporting
confidence: 71%
“…Recently, our group published detailed clinical, molecular, and radiological features of 12 new subjects with El-Hattab-Alkuraya syndrome (Almannai et al, 2022). Similar to what was observed in the initial report, the main features of this syndrome in this cohort are GDD, spastic quadriplegia, microcephaly, and early onset and refractory epilepsy (Almannai et al, 2022). Furthermore, neuroradiological findings in this syndrome are homogenous, especially among individuals with loss-offunction variants and therefore four criteria were proposed that could suggest the diagnosis of El-Hattab-Alkuraya syndrome.…”
Section: Wipi (Wdr B)mentioning
confidence: 99%
See 1 more Smart Citation
“…As WDR45 and WDR45B were also reported associated with development delay, for example, J Suleiman et al described a homozygous pathogenic variant (c.673C>T, p.R225*) in two families. The probands exhibited profound development delay, early‐onset refractory epilepsy, progressive spastic quadriplegia, contractures, and brain malformations (Suleiman et al, 2018); Najmabadi et al reported a homozygous missense variant (R109Q) from three members of a closely related family with intellectual disability and microcephaly (Najmabadi et al, 2011); Almannai et al presented 12 individuals from seven unrelated families with microcephaly, global developmental delay, seizures, and spastic quadriplegia (Almannai et al, 2022). These studies demonstrated the role of WDR45B in neurodevelopmental diseases.…”
Section: Discussionmentioning
confidence: 99%
“…To date, variants in WDR45B are rare, and clinical features are relatively heterogeneous. Only two homozygous nonsense variants (c.799C>T (p. Q267*); c.673C>T (p. R225*)), three splicing variants (c.619‐3A>G; c.427+4A>G; c.67+1G>T), one frameshift variant (c.428‐10_435del18), and two missense variants (p. R109Q; p.R225Q) of WDR45B have been identified in 11 families (Almannai et al, 2022; Najmabadi et al, 2011; Suleiman et al, 2018).…”
Section: Introductionmentioning
confidence: 99%